Substrate Treatment Evaluation and Their Impact on Printing Results for Wearable Electronics - Khan, Saleem; Ali, Shawkat; Khan, Arshad; Wang, Bo; Al-Ansari, Tareq; Bermak, Amine (Frontiers in Electronics, 2021)
This paper presents a comparative study on the treatment techniques for flexible polymeric substrates and their impact on the printing results. Substrate treatments are central to optimization of the printing processes and a strict set of requirements are needed to achieve uniform and acceptable printing results. Therefore, this research is highlighting the most significant treatment methods used for fine-tuning the surface properties of different polymeric substrates. Besides the two commonly used treatment techniques of oxygen plasma and UV ozone, a new method of using surface cleaning liquid is applied for rapid treatment of polymeric substrates. Comparative study is carried out on the basis of cleaning steps required for substrate preparation, processing, robustness as well as on the final printed results on the substrates. All the three treatment techniques with similar processing protocol are applied on a single type of polyimide (PI) substrate. To further validate the applicability and manufacture of practical devices, the liquid cleaning method is also applied on PET substrates for making proof-of-concept wearable temperature sensor. From the study it is concluded that the liquid surface cleaning method is advantageous in terms of easy processing, robustness and producing uniform printing results on diverse polymeric substrates.